Predicting the strengths of basalt fiber reinforced concrete mixed with fly ash using AML and Hoffman and Gardener techniques - Kennedy C. Onyelowe; Viroon Kamchoom‬; Shadi Hanandeh; Ahmed M. Ebid; José Luis Llamuca Llamuca; Juan Carlos Cayán Martínez; Evlin Rose; Paul O. Awoyera; Siva Avudaiappan (Scientific Reports, 2025)
of 0.96 for training and validation phases. Its exceptionally low validation MAE of 0.124 MPa underscores its excellent generalization capabilities. Overall, XGBoosting and AdaBoost consistently demonstrate superior performance for both compressive and splitting tensile strength predictions, followed closely by KNN. These models benefit from advanced ensemble techniques that efficiently handle non-linear patterns and noise. SVR also performs admirably, whereas GEP and GMDHNN exhibit weaker predictive capabilities due to limitations in handling complex data dynamics. For the sensitivity analysis, the Hoffman and Gardener's method of sensitivity analysis proves instrumental in identifying key drivers of strength in fiber-reinforced concrete, guiding informed decision-making for material optimization and sustainable construction practices.
Keywords: Innovative concrete reinforcement materials; Concrete and Cement Materials Research; Infrastructure Maintenance and Monitoring